Analysis of the setter's tactical action in high-performance women's volleyball - Afonso, J.; Mesquita, I.; Marcelino, R.; da Silva, J. A. (Kinesiology, 2010)
Performance analysis is of fundamental importance to understand the factors underlying participation in top-level sports. Recently, an increased importance has been given to the preservation of the situation`s ecology, thus attempting the comprehension of game patterns through the establishment of relationships between variables of several orders. The purpose of this study was to analyse some match variables that could constraint the setter`s tactical action in high-performance women`s volleyball, as well as its outcomes. Six matches of the Women`s World Champhionships 2006 were analysed following a category system, recurring to observational methodology, namely the technique of sequential lag analysis. Attack tempo has emerged as the crucial variable of the setter`s tactical action. Patterns with closed blocks from the opponent, setting in the ideal zone with a jump set, attack simulation by the middle attacker and block anticipation, through committing strategies, tended to culminate in quick attacks. These, in turn, stimulate a debilitated block opposition. Open block formations, receptions in zones 4 and 1, setting in non-ideal zones, no simulation by the middle attacker and a non-anticipative block (read-and-react strategy) stimulated slow attacks, which, in turn, stimulated cohesive block opposition. Attack efficacy emerged as independent of the setter`s action, although the latter largely influenced the type of block opposition. Hence, match analysis provides a window into aspects involving the tactical actions in high-level athletes.